An interpolation result for A_1 weights with applications to fractional Poincaré inequalities - Drelichman, Irene (Annales Fennici Mathematici, 2024)
We characterize the real interpolation space between weighted \(L^1\) and \(W^1,1\) spaces on arbitrary domains different from \(R^n\), when the weights are positive powers of the distance to the boundary multiplied by an \(A_1\) weight. As an application of this result we obtain weighted fractional Poincaré inequalities with sharp dependence on the fractional parameter \(s\) (for \(s\) close to 1) and show that they are equivalent to a weighted Poincaré inequality for the gradient.